The Diamond Project: A Quality Improvement Model for Adopting Shared Service Delivery in the Washington Vaccines for Children Program - Bekemeier, Betty; Delaney, Kylerose; Wenzl, Stacy; Roberts, Michele; Hersh, Dorene (Frontiers in Public Health, 2020)
Context: Increasing federal requirements with no change in the Centers for Disease Control and Prevention budget creates an unsustainable delivery model between states and their local counterparts for programs like Vaccines for Children (VFC). Project: The Washington State Department of Health collaborated with the Washington Association of Local Public Health Officials to identify how best to improve the quality of the VFC program. Approach: Utilizing Quality improvement and Lean Six Sigma methods, the project team was able to adopt a new shared-service delivery model to improve the quality of the VFC program in Washington State. Discussion: Through utilization of quality improvement methods and Lean methodology Washington State Department of Health identified recommendations to adopt a shared-service delivery and implemented those changes.